HUBUNGAN PENINGKATAN TNF-Î± DAN LEUKOSIT DENGAN KEJADIAN INFEKSI LUKA OPERASI PASCA OPERASI MAYOR DI RSUP Dr. SARDJITO - , Sri Utami; , dr. Supomo, Sp.B(K)BTKV. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Surgical site infection (SSI) is one of surgical complication which mostly happens. Surgical site infection is defined as a condition where pus, abscess or expanding cellulitis is found on the surgical site within 30 days post-operatively or within 1 year after implant surgery. Among all nosocomial infections reported around the world, 20-25% of them are surgical site infections. To diagnose a bacterial infection, it mostly uses clinical data, white blood count, blood culture, or pus culture, which needs a long time to proceed and cause a delayed therapy. Thus, we need another diagnostic method which results faster to indicate any surgical site infection (SSI). This study was a descriptive analysis with an observational prospective design. Patients who underwent major surgeries during October 2011 until December 2011, were informed consent and had their clinical condition and white blood count examined before surgery. Patients who were included in the criteria were followed up to 30 days after surgery. On the third day after surgery, the patients had their white blood count and serum TNF-Î± checked. Patients who were included in to the SSI criteria based on Centers for Disease Control (CDC) United State of America underwent culture examination from their surgical wound. The purpose of this study was to understand the correlation between the increase of serum TNF-Î± and white blood count with the incidence of SSI. There were 45 patients included in the criteria, which consisted of 20 males and 25 females. We found 16 cases (36%) of SSI, which consisted of 12 cases superficial type-SSI and 4 cases deep type-SSI. Laboratory examination on the third day after surgery showed that there were 11 patients with abnormal white blood count